Ewolucja środków płatności (zapłaty): od pieniądza gotówkowego do pieniądza elektronicznego: [The development of payment methods: From cash money to electronic moneys] (Studia Prawnicze / The Legal Studies, 2012)
W toku rozwoju cywilizacyjnego postać pieniądza, jako miernika wartości dóbr i usług podlegających wymianie rynkowej, a zwłaszcza środka płatności (zapłaty) i umarzania zobowiązań przeszła znamienną ewolucję, od pieniądza „towarowego” i gotówkowego do form coraz bardziej konwencjonalnych i abstrakcyjnych, takich jak pieniądz elektroniczny, który staje się symbolem ery elektronicznej.Pieniądz jest częścią cywilizacji. Wyłonił się w rezultacie umowy społecznej, ponieważ w danym miejscu i czasie był środkiem ułatwiającym wymianę (zapłatę), powszechnie akceptowanym przez społeczeństwo.Poszczególne etapy rozwoju pieniądza są ściśle związane z rozwojem gospodarczym społeczeństwa oraz globalnym postępem technologicznym, a także – z rozwojem banków. Pieniądz przybierał coraz to nowe formy, które były efektywniejsze od starych i pozwalały lepiej spełniać podstawowe funkcje pieniądza. Rozróżnianie postaci pieniądza wiąże się z różnymi sposobami płatności (zapłaty).Główną funkcją pieniądza jest ułatwianie dokonywania transakcji między podmiotami gospodarczymi, a zwłaszcza dokonywanie płatności (zapłaty) w celu umarzania zobowiązań, nie mówiąc o akumulacji kapitału. Money has existed in civilization for thousands years. The development of money has passed through various stages in accordance with time, place and circumstances. Primitive money took many forms, from cowrie shells to cattle and later transformed into metallic money (like gold, silver, copper, bronze, etc.) The continued development of money was very much linked to the growth in world trade and commerce. Next to cash came up non-cash payment transactions, mainly with credit or debit card. Money serves three purposes. First, it serves as a medium of exchange. Second, as a standard of value, it serves as a measure for the value of a good or service and thus provides a standard for making comparisons between different goods and services. Third, it must be widely accepted. The larger the community of users who trust and accept money, the more that its value as a medium of exchange is increased. Finally, when it is exchanged, there is anonymity. Rapid advances in technology, including Internet have made a lot of changes in payment methods. Technological innovations convert money into something more virtual than physical. Electronic money (e-money) is the digital equivalent of cash. It can be used for making payments without involving bank accounts in the transactions and always acts as a prepaid bearer instrument. E-money can be software or hardware based. One common type of hardware-based e-money is the ‘electronic purse’, where users store relatively small amounts of money on the chip or magnetic stripe of their payment card, other smart card or on mobile phones, to make small payments. Another option is to store e-money in a payment account on the Internet (software based). In general, e-money should be characterized as a substitute for currency (cash) The development of innovative e-money raises numerous legal and regulatory issues that must be addressed. These include finding acceptable methods for authentication and protection of information, accommodating the special needs of law enforcement, and creating the requisite means of settling disputes. The progressive development of technology and communication, harmonization of currency systems and becoming more common use of electronic instruments may create the uniform (European) system of electronic money. That would made e-money the legal tender with the force of redemption obligations.